Peramalan Jumlah Siswa Baru Madrasah Aliyah (MA) Manhalul Ma’arif Darek-Lombok Tengah - Lisa Harsyiah; Nurul Fitriyani; Salwa Salwa (University of Mataram, 2020)
This study aimed to forecast the new student number at Madrasah Aliyah (MA) Manhalul Ma'arif Darek. The data used in this study was the annual time series data of new students who enrolled in the school, from the 1998/1999 academic year to 2016/2017. Based on the data obtained, it shows that the number of new students who enroll in Madrasah Aliyah (MA) Manhalul Ma'arif Darek tends to fluctuate. This fluctuating pattern is a problem faced by Madrasah Aliyah (MA) Manhalul Ma'arif Darek in determining strategic and policy steps related to planning the provision of school facilities / infrastructure. Therefore we need a forecasting method in accordance with the data pattern. The forecasting method used is the Fuzzy Time Series Cheng method. This method uses fuzzy principles as the basis of the forecasting process. The forecasting process results obtained the Mean Square Error (MSE) value of 101.5009 and the Mean Absolute Percentage Error (MAPE) value of 18.49%. The results showed that the Fuzzy Time Series Cheng method performed well in predicting the number of new students at Madrasah Aliyah (MA) Manhalul Ma'arif Darek.